Emerging capital markets and globalization : - Torre, Augusto de la (The World bank, 2007)
This book sheds light on the analytical, empirical, and policy dimensions of a basic stylized fact - that the development of local capital markets in most of Latin America has been quite poor relative to other emerging economies and to global trends. Importantly, it discusses the implications for the capital market reform agenda going forward, emphasizing the need for revisions to the prevalent policy paradigm.